TGF‐β Signaling Plays a Pivotal Role During Developmental Biliary Atresia in Sea Lamprey (Petromyzon marinus) - Yu‐Wen Chung‐Davidson; Jianfeng Ren; Chu‐Yin Yeh; Ugo Bussy; Belinda Huerta; Peter Joseph Davidson; Steven Whyard; Weiming Li (Hepatology Communications, 2020)
Biliary atresia (BA) is a rare neonatal disease with unknown causes. Approximately 10% of BA cases develop in utero with other congenital defects that span a large spectrum of disease variations, including degeneration of the gall bladder and bile duct as well as malformation of the liver, intestines, and kidneys. Similar developmental alterations are manifested in a unique animal model, the sea lamprey (Petromyzon marinus), in which BA occurs naturally during metamorphosis. With the likelihood of conserved developmental mechanisms underlying organogenesis and degeneration, lamprey developmental BA may be a useful model to infer mechanisms underlying human embryonic BA. We reasoned that hepatobiliary transcriptomes regulate the transition between landmark stages of BA. Therefore, we examined sea lamprey hepatobiliary transcriptomes at four stages (M0, metamorphic stage 0 or larval stage, no BA; M2, metamorphic stage 2, onset of BA; M5, metamorphic stage 5, BA, and heightened hepatocyte proliferation and reorganization; and JV, juvenile, completion of BA) using messenger RNA sequencing and Kyoto Encyclopedia of Genes and Genomes pathway analyses. We found gene‐expression patterns associated with the transition between these stages. In particular, transforming growth factor β (TGF‐β), hedgehog, phosphatidylinositol‐4,5‐bisphosphate 3‐kinase‐Akt, Wnt, and mitogen‐activated protein kinase pathways were involved during biliary degeneration. Furthermore, disrupting the TGF‐β signaling pathway with antagonist or small interfering RNA treatments at the onset of BA delayed gall bladder and bile duct degeneration. Conclusion: Distinctive gene‐expression patterns are associated with the degeneration of the biliary system during developmental BA. In addition, disrupting TGF‐β signaling pathway at the onset of BA delayed biliary degeneration.